Pengaruh Perencanaan Pajak, Ukuran Perusahaan dan Profitabilitas Terhadap Manajemen Laba Pada Perusahaan Sektor Konsumen Non-Primer yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2021 - Charles Theo Tri Mewati (Jurnal Akuntansi, 2023)
The purpose of this study is to examine the impact of tax planning, frm size, proftability on earnings management. The research method used in this research is quantitative using the Eviews program version 10. The data used in this study uses secondary data in the form of company financial reports in the non-primary consumer goods sector which are listed on the Indonesia Stock Exchange in 2018- 2021 periode. the sample selection in this study used a purposive sampling methode. The results of this study indicate that (1) tax planning has no signifcant eﬀect on earnings management, (2) frm size has a signifcant eﬀect on earnings management, (3) Proftability has no signifcant eﬀect on earnings management. Keywords: tax planning, frm size, proftability, earnings management.